Literature, Covid-19 and Human Greed: A Socialist Realism Analysis of Taufiq al-Hakim’s Short Story “Daulah al-‘As}a>fi>r” - Zulhelmi Zulhelmi (Buletin Al-Turas, 2021)
The article aimed to discover whether the element of Taufiq al-Hakim's imagination regarding human greed had relevance to the social reality of society, or is it merely an expression of personal imagination that was not related to the social environment of society? To answer this problem, the researcher used the text analysis method with the main corpus of the short story “Daulah al-‘As}a>fi>r.” The theory used in analyzing this text was socialist realism assisted by a literary ecological approach. The analysis showed that Taufiq al-Hakim's imaginative criticism through his sparrow symbol against human greed had a close relevance to the phenomenon of contemporary human life today, like Covid-19 pandemic. Such pandemic was a natural reaction to human greed who had exploited fellow humans and their environment. It was also reinforced by the fact that all big and powerful countries in the world were overwhelmed to overcome Covid-19. This study recommended that humans should not be greedy, so that the balance of nature can be maintained properly.